LINGUOCULTURAL ANALYSIS OF PHRASEOLOGICFAL UNITS IN EASTERN CULTURE - qizi, Aliyeva Sarvinoz Abbosjon; Toirova, N. (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
Introduction. It is critical not to disregard human-related difficulties when studying phraseology from an anthropological viewpoint, as correct anthroponymic components of phraseological units were studied in an anthropocentric manner in the study of phraseological units. Anthroponyms have a unique place in the language because of their semantic and methodological characteristics, which set them apart from other lexical units. This necessitates undertaking synchronous and diachronic onomastic research based on comparative-historical research. The phraseological units connected with nouns do, in fact, have social importance and reflect a society's culture and social life. The system of images embedded in the language's phraseological structure, in turn, serves to express people's national-cultural experiences and customs. Research methods. Within the framework of a linguistic view of the world based on system-structural paradigms, the study used component and stylistic analysis approaches. Phraseological units are distinguished from other language units in that they give speech imagery, expressiveness, and emotionality. The definition of national and cultural elements of phraseological units with anthroponic components of the Uzbek language, representing various socio-cultural cultures of the East, receives the most attention. Results and discussions. The study of determining the sources of origin of phraseological units in the Uzbek language with anthroponymic components on the basis of phraseological units associated with traditional names, national folklore, people's history, real historical figures and characters from literary works is a scientific novelty. As a result, it was determined that the system of images in the composition of phraseological units is linked to the nation's physical, social, or spiritual culture, as well as the formation of its worldview, and thus they gain special significance because they contain information about the nation's national and cultural experience, traditions, and customs. Conclusion. Phraseological units connected with traditional names, national folklore, people's history, names of real historical persons, and characters from literary works are used to determine the sources of origin for phraseological units with anthroponymic components in Uzbek languages.